L'Inferno. Nacque Dante A: MCCLXV. Mori Dante A: MCCCXXI. - Carus, Carl Gustav,Williard, Johann Anton,Dante (Königl. Steindruckerei, 1829)
Topographischer Abriß von Dantes Inferno mit allen 11 Umkreisen
Lithographie